2017
DOI: 10.1103/physrevb.96.235124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stoichiometry and disorder on the electronic structure of the PbBi2Te4xSex topological insulator

Abstract: Detailed comparative theoretical and experimental study of electronic properties and spin structure was carried out for a series of Pb-based quaternary compounds PbBi 2 Te 4−x Se x. For all values of x, these compounds are theoretically predicted to be topological insulators, possessing at high Se content a remarkably large band gap and a Dirac point isolated from bulk states. Using spin-and angle-resolved photoemission spectroscopy, it was shown that the PbBi 2 Te 2 Se 2 and PbBi 2 Te 1.4 Se 2.6 compounds are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…As was shown theoretically in Ref. [14], in the SL PbBi 4 Te 4−x Se x compound the substitution of Te by Se, in addition to a significant increase of the bulk band gap (from 90 meV for x = 0 up to 220 meV for x = 2), leads to redistribution of the charge density of TSS, shrinking its depth profile. Thus, in the heterostructures, containing alternating QL and SL with Se content, the band gap is expected to be larger and TSS to be localized closer to the surface with shorter penetration length.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…As was shown theoretically in Ref. [14], in the SL PbBi 4 Te 4−x Se x compound the substitution of Te by Se, in addition to a significant increase of the bulk band gap (from 90 meV for x = 0 up to 220 meV for x = 2), leads to redistribution of the charge density of TSS, shrinking its depth profile. Thus, in the heterostructures, containing alternating QL and SL with Se content, the band gap is expected to be larger and TSS to be localized closer to the surface with shorter penetration length.…”
Section: Introductionsupporting
confidence: 54%
“…Due to unique properties, TSSs are of great interest for the observation of many novel quantum phenomena, in particular, quantum spin Hall effect and quantum anomalous Hall effect [3]. So far, a wide variety of compounds hosting spin-polarized TSSs have been thoroughly studied [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. After the discovery of narrow-gap tetradymite-type semiconductors with quintuple-layer (QL) crystal structure [4][5][6], further efforts at controlling the electronic structure of TIs and TSSs led to fabrication and study of septuple-layer (SL) compounds [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Recent studies have shown that some of these phases are topological insulators and are considered promising for use in spintronics and quantum computing. [8][9][10][11] Among the chalcogenide materials, magnetic semiconductors of the type MB 2 X 4 (where M -Mn, Fe, Co, Ni; B -Ga, In; X -S, Se, Te) and phases on their basis are very promising for use in the manufacture of lasers, light modulators, photodetectors and other electronic devices controlled by a magnetic field. [12][13][14][15][16][17] Search and development of methods for the directed synthesis of new multicomponent phases and materials requires the study of phase equilibria in the relevant systems.…”
Section: Introductionmentioning
confidence: 99%
“…Tellurides of heavy metals, as well as complex phases and composites based on them, are promising functional materials for electronic engineering [1][2][3][4]. Recent studies have shown that many binary and complex tellurides with tetradimite-like layered structure are topological insulators and can be used in spintronics and quantum computing [5][6][7]. Some complex silver tellurides possess ionic conductivity over the Ag + cation and can be used as electrochemical sensors, electrodes or electrolyte materials in electrochemical energy conversion devicesin solid-state batteries, displays etc.…”
Section: Introductionmentioning
confidence: 99%